2018
DOI: 10.3892/ol.2018.7839
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of thoracoscopic surgery in the treatment of lung cancer in the perioperative period and its effects on serum D-dimer

Abstract: The aim of this study was to investigate the feasibility and safety of thoracoscopic surgery in the treatment of lung cancer and its effect on serum D-dimer. A total of 218 patients with lung cancer treated in the Department of Thoracic Surgery of Ningbo No. 2 Hospital from January 1, 2013 to December 31, 2016, were retrospectively analyzed. Of the 218 patients, 120 patients underwent thoracotomy (thoracotomy group) and 98 patients underwent thoracoscopic surgery (thoracoscopy group). The clinical efficacy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The possible reasons to explain the benefit would be the effect of less anesthesia stimulation and less muscle relaxant. Previous findings have shown that the increase in serum D-dimer in open procedures was more obvious than that in the thoracoscopy group, 20 indicating a lower level of D-dimer change was associated with a more minimally invasive approach. Further prospective study should be conducted to validate the potential advantage of spontaneous ventilation on prevention of venous thrombus.…”
Section: Commentmentioning
confidence: 83%
“…The possible reasons to explain the benefit would be the effect of less anesthesia stimulation and less muscle relaxant. Previous findings have shown that the increase in serum D-dimer in open procedures was more obvious than that in the thoracoscopy group, 20 indicating a lower level of D-dimer change was associated with a more minimally invasive approach. Further prospective study should be conducted to validate the potential advantage of spontaneous ventilation on prevention of venous thrombus.…”
Section: Commentmentioning
confidence: 83%
“…D-dimer levels >0.55 mg/l were considered to be elevated, since this was the upper limit of the 90% confidence interval for the average value determined in the healthy volunteers. The D-dimer levels in tumor patients can be affected following surgery (25,26), chemotherapy (27,28) and adjuvant therapy (29). Therefore, the data analyzed herein is the D-dimer expression level of all patients prior to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with thoracotomy, multiportal VATS significantly reduces surgical trauma and postoperative complication rates and improves the quality of life after surgery 26 . Multiportal VATS is also significantly superior to thoracotomy in terms of the rates of surgical incision infection and postoperative cardiac and pulmonary complications 27–29 . This study shows that the rates of postoperative and pulmonary complications were similar between the groups.…”
Section: Discussionmentioning
confidence: 61%